Oscillating hypothyroidism and hyperthyroidism - a case-based review - WuQiang Fan; Prabhat Tandon; Mahesh Krishnamurthy (Greater Baltimore Medical Center, 2014)
Objective/Background: To discuss a unique clinical entity where inappropriate activity of inhibitory and stimulatory thyroid antibodies resulted in alternating hypothyroidism and hyperthyroidism. Methods: We report the clinical history, laboratory data, and results of imaging studies, along with the pathophysiological mechanism and the subsequent treatment in a patient with fluctuating thyroid functional status. Results: A 52-year-old female was treated for hypothyroidism for more than two decades. She started having symptoms of hyperthyroidism along with a suppressed thyroid-stimulating hormone (TSH). She continued to have persistent symptoms despite stopping her levothyroxine. Her free T3 and T4 were elevated along with an increased radioactive uptake scan. She was diagnosed with Graves' disease and started on methimazole, which relieved her symptoms for a few months. Subsequently, her TSH began to rise beyond expected level, her hypothyroid symptoms reappeared, and methimazole was discontinued. Following this, she again developed symptoms of hyperthyroidism and thyroid values revealed an undetectable TSH. She had at least two such documented cycles of hyperthyroidism alternating with hypothyroidism. She was eventually treated with radioactive iodine ablation followed by levothyroxine replacement. Swinging dominance of TSH-blocking autoantibodies (TBAb) and thyroid-stimulating autoantibodies (TSAb) triggered by methimazole and levothyroxine, respectively, is likely the underlying mechanism. Conclusions: Physicians should be vigilant to the phenomenon of spontaneous conversion of hypothyroidism to hyperthyroidism, or vice versa, in a subset of patients with autoimmune thyroid disease. Repeated assessment of thyroid function along with measurement of TBAb and TSAb are invaluable in identifying this rare clinical entity.